A New Proposal of Hebrews’ Outline - Najoan, Jemmy C. (8ISC Proceedings: Theology, 2022)
Identifying and understanding the outline of a book in the Scripture is important to understand a text. One book in the Scripture that receives attention from scholars in terms of inquiring about the outline or the structure of its book is the Book of Hebrews. This is due to the awareness among scholars in regard to the complexity of this book’s outline or its structure. Because of its complexity, scholars have proposed various outlines of this book. In fact, by careful study, a new approach of even the idea of the outline of Hebrews could be brought to the surface. Therefore, using some aspects of the literary devices proposed by Alberth Vanhoye, this paper task was to analyze the way how the author composes the book of Hebrews and provide a new outline of this book. In turn, this new outline provided help for interpreters to exegete this book. Keywords: Hebrews, outline, complexity, new approach, literary devices.